Determination of efficacy of curcumin and Tulsi extracts as local drugs in periodontal pocket reduction: A clinical and microbiological study - Apurva Rahalkar; Kanteshwari Kumathalli; Rajesh Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: The aim of our study is to assess the effectiveness of Curcumin and Tulsi in the control of periodontal parameters when delivered in the form of local drug delivery (LDD) agents. Methods: Curenext gel® and Tulsi gel were used as the two LDD agent. A split mouth randomized clinical trial was carried out in 15 patients. Three sites in different quadrants were assigned treatment modality of scaling and root planing (SRP) alone, SRP with LDD of curcumin and SRP with LDD of Tulsi extract, respectively. Clinical parameters Probing Pocket Depth, Clinical Attachment Level, Plaque Index, Gingival Index, and modified Sulcus Bleeding Index were recorded and subgingival plaque sample collected for N-benzoyl-L-arginine-p-nitroanilide (BAPNA) assay on baseline followed by LDD with extracts in the assigned group. The parameters were recorded at baseline and on 30th day postoperatively. Unpaired and Paired-'t' test were used for intergroup and intragroup comparison of recorded clinical and microbiological parameters. Results: All the treatment modalities showed statistically significant reduction in clinical and microbiological parameters on intragroup comparison. Intergroup comparison showed statistically significant reduction in Plaque Index in curcumin group and BAPNA assay in Tulsi group when compared to SRP. Conclusion: Both the herbs were effective in improving periodontal parameters and may develop as an alternative to currently used LDD agents in near future.